Ketorolac tromethamine inhibits inflammation in rat models with knee osteoarthritis - LI Rong, ZHU Han-yue (Jichu yixue yu linchuang, 2022)
Objective To investigate the effect of ketorolac tromethamine (KT) on the inflammatory pain caused by knee osteoarthritis (KOA) of rat model and to explore potential mechanism related to Toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) inflammatory pathway. Methods The rats were divided into: control group, model group, low (1 mg/kg),high (4 mg/kg) dose KT group,TAK-242 group (TLR4 antagonist,1 mg/kg) by random number table method; Except for the control group, the other groups used the modified Hulth method to replicate the KOA model of the right knee in rats; KT was administered by intramuscular injection once a day, and TAK-242 was administered by tail vein injection twice a week. The swelling and activity of the knee joint of the rats were recorded, and the spontaneous pain behavior gait and the thermal pain threshold were measured; the synovial tissue was sampled, and the histopathological changes and fibrous tissue proliferation were detected by microscopy with HE staining and Masson staining; The expression of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α),neuritin expression and the TLR4,NF-κB,phosphorylated NF-κB (p-NF-κB),osteopontin (OPN),integrin metalloproteinase 4 (ADAM4) proteins expression in synovium tissue were detected. Results Compared with the control group, the model group rats had more severe pathological symptoms of KOA, such as joint swelling, pain, synovial inflammatory damage and fibrous tissue hyperplasia, the IL-1β and TNF-α levels and the neuritin expression,the TLR4/NF-κB p65 pathway and related proteins OPN,ADAM4 expression in synovium increased (P＜0.05).Compared with model group, the pathological symptoms such as KOA pain and synovial inflammation of rats in low, middle and high dose KT groups were alleviated, the TLR4/NF-κB p65 pathway and related proteins expression in synovium decreased (P＜0.05). Conclusions KT can relieve the synovial inflammation and pain symptoms of KOA rats; Its relieving effect may be related to blocking the activation of TLR4/NF-κB pathway.